Manufacturing a Monster: an autoethnographic analysis of enforced isolation, objectification and the destruction of self - Quinn, Alexis (Frontiers in Psychiatry, 2025)
IntroductionThis perspective article examines the impact of enforced isolation on the authors sense of Self. The research explores how systemic objectification and the blocking of vital “mirroring” within seclusion and long-term segregation (LTS) in psychiatric hospitals in England can lead to the erosion of Self. The paper posits that enforced isolation is not therapeutic, but a destructive intervention rooted in neuronormative ideology that ultimately escalates distress, prolonging detention.MethodsThe autoethnographic perspective offers a qualitative understanding of experience to examine the phenomena of isolation and trauma. The reflexive analysis is rooted in the author’s lived experiences of repeated and enduring exposure to seclusion and LTS.ResultsEnforced isolation eroded the author’s Self due to systemic objectification and a lack of positive “mirroring”. Consequently, the Self could only be sustained through perverse connections with staff e.g., shared negative emotions such as fear, aggression and hate. With a Self-reconfigured around negative affect, the lines are blurred between intimacy and aggression, resulting in shattering implications for the author’s ability to have relationships and love.DiscussionEnforced isolation is positioned as a destructive intervention, manufacturing rather than containing, distress. This perspective reframes isolation from a clinical tool to a harmful practice, contradicting therapeutic goals. Aligning with wider research, the paper calls for a transformative shift towards rights-based, relational models, such as HOPE(S), that prioritize human connection to prevent iatrogenic harm.